Catalytic conversion of glucose to ethyl lactate over zeolite - Panipuk Maneethai (Chulalongkorn University, 2020)
Conversion of glucose to ethyl lactate was conducted using retro-aldol reaction using various types of catalysts. In this report conversion of glucose via retro-aldol reaction was conducted with different catalysts. Beta and other catalysts were synthesized and impregned with a direct and wet impregnation method with Niobium as metal oxide for the supported catalyst in order to increase Lewis acid. All catalysts were investigated for their identity and presence of Niobium using X-ray diffraction (XRD). The reaction was conducted mainly at 200 °C in a 25 mL Parr reactor for 1 hour. Gas chromatography (GC) was used to investigate carbon based yield of the ethyl lactate which is the main product of reactions. The result showed the reaction that conducted with impregnation zeolite uses less metal oxide than separately add metal oxide for 4.4 times and still gives higher percent of carbon based yield. As a result Nb-MCM-22 gives out 26% yield of ethyl lactate and the catalyst that gives the highest yield is Nb- Beta zeolite which gives out 32%.